On the Size of Dominant Momentum Transporting Eddies in Stable Atmospheric Boundary Layers - Xin Shao; Ning Zhang; Dan Li; Jianning Sun (Geophysical Research Letters)
Abstract The size of dominant momentum transporting eddies Lmt in stable atmospheric boundary layers is poorly understood. This study demonstrates that the distance to the ground z is relevant in constraining Lmt in weakly stable conditions (0<ζ<0.6, where ζ is the stability parameter) and less relevant in moderately stable conditions (0.6<ζ<2.0). The widely used Ozmidov scale, however, fails to represent Lmt in moderately stable conditions. The low‐wavenumber ends of the −5/3 scaling law regions in the spanwise and vertical velocity spectra correlate better with a shear‐related length scale. Based on the characteristics of velocity spectra and the balance between kinetic energy and potential energy, a new length scale is proposed to indicate Lmt for moderately stable conditions. Observational data show that this new length scale effectively characterizes Lmt in moderately stable conditions. These findings can help develop better turbulence parameterization schemes for stable atmospheric boundary layers.